Analisis Butir Soal Pilihan Ganda Ujian Akhir Semester Ganjil Tahun 2016/2017 Mata Pelajaran Ekonomi Kelas XII Di SMA Swasta Sesurakarta - Azizah, Rizki Nur; , Suranto S.Pd., M.Pd (2017)
Ratings were good views of the process of planning, implementation and evaluation. This study aimed to evaluate the question Final Exam Subjects Economic intended to measure the ability of students to understand the material. This study analyzes the items based on 1) the validity, 2) reliability, 3) level of difficulty, 4) distinguishing, and 5) the suitability matter with SK and KD. This research is quantitative descriptive and non-experimental research design that making random population. The population is the entire private high school in Surakarta XII class that uses questions that have been designed by BKS (Private High School Cooperation Agency) in Surakarta. The sample used in this research is purposive samplingwith the school as much as9. As for the data collection techniques by means of unstructured interviews and documentation in the form of questions, answer sheet and answer key questions. Data analysis using SPSSv24.0. The results showed, (1) the validity of the economy generates about 96% valid, the issue of Accounting Package A 86.67%, and about Accounting package B is 80%; (2) Problem Economics, Accounting Package A and B shows the overall reliability is a matter of having a moderate level of reliability category with a coefficient of 0.40 <R count <0.70 respectively in the range of 0,495 coefficients; 0.405; and 0,535; (3) the difficulty level items overall economy is 28% difficult, 56% moderate, and 16% easy; A matter of accounting packages have a hard level of difficulty of 20%, 73.3% moderate, 6.7% easy; and about Accounting packages B 20% difficult, 80% medium and 0% easy; (4) distinguishing acceptable economic problems was 52%, about 73.3% Accounting package A and package B Accounting matter has 80% about acceptable; (5) compliance with SK and KD matter does not fit the overall economy; Accounting questions about the appropriate package A 10; Accounting matter B 8 corresponding package.